Moral Value-Based Lecturer Spiritual Leadership Model In Improving Students' Emotional Intelligence - Fandir, A.; Nurfidah, Nurfidah (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study explores the role of spiritual leadership based on moral values applied by lecturers in improving students' emotional intelligence. By prioritising values such as integrity, honesty, empathy, and exemplary behaviour, lecturers function not only as academic educators but also as moral role models who shape students' character. This study shows that spiritual leadership creates a harmonious, supportive academic environment that focuses on students' moral and emotional development, which ultimately affects their academic achievement, social skills, and critical thinking skills. The study was conducted through a qualitative approach in a higher education environment, using in-depth interviews, FGDs, and observations. The results confirm that this leadership model has a positive impact on the development of students' emotional intelligence, which is very relevant to their academic success and professional lives. The study recommends that educational institutions support lecturers through spiritual leadership training and emotional intelligence development, as well as integrating moral activities such as ethical discussions and community service programs to strengthen students' character.